ANALYSIS OF ATTENTION DEFICIT HYPERACTIVITY DISORDER IN RELATION TO LEGISLATION, EDUCATION AND PSYCHIATRIC ASSISTANCE - Peruchi Machado, Túlio; Carlos Illafont Coronel, Luis; Silva de Souza, Wagner (Health and Society, 2023)
ADHD (attention deficit hyperactivity disorder / hyperactivity) is a chronic neurobiological disorder whose main characteristics are: inattention, hyperactivity and impulsivity. These are signs that manifest in childhood and they may last for a lifetime if not properly identified and treated. The main objective of this scientific paper is to seek a critical review of the law which covers the inclusion of people with such special needs, also, to observe how the school has behaved in the face of this problem and what the essential elements are concerning the diagnosis and the therapeutic approaches to ADHD. The exploratory research has been made for a deeper understanding of the subject and to make it more explicit, which ended becoming bibliographic research, reaching a literature review in order to contribute to the understanding of the theme. As results achieved, it was realized that this disorder is a psychiatric syndrome of high prevalence in children and adolescents, being covered by the current law in the country. The school has not learned to live with this kind of problem yet, though it is important in contribution to the data collection, along with the parents and the child. It was concluded that the ADHD treatment reaches a multiple approach involving psychosocial and psychopharmacological interventions, being medication the most effective use for this disorder.